Analisis Mutu Penyelenggaraan Pendidikan dan Pelatihan Kesehatan Oleh UPT Bapelkes Dinas Kesehatan Provinsi Riau - Islamiyah Islamiyah; Irwan Muryanto; Abdurrahman Hamid; Jasrida Yunita; Reno Renaldi (STIKes Hang Tuah Pekanbaru, 2021)
The ability of the UPT health training center for Riau Provincial Health Office in providing education and health training was faced with several problems. The objective of the research was to analyze the implementation of health education and training by the UPT Bapelkes Riau province. The design of this research is qualitative. The tringulations that used were source tringulation, method and data. The results showed that the tangible dimensions for facilities and infrastructure were still not good enough, the human resources and staff appearance were quite good. Reliability was good enough. Responsiveness was good enough. Assurances were good and empathy was good. Suggestion for UPT Bapelkes Riau province to complete facilities and infrastructure as well as carried out quality safety and quality assurance.